The aesthetics of disappearance - Virilio, Paul.; Beitchman, Philip, 1939- (Los Angeles, CA : Semiotext, 2009)
Focusing on the logistics of perception, this title introduces the author's understanding of 'picnolepsy' - the epileptic state of consciousness produced by speed, or rather, the consciousness invented by the subject through its very absence: the gaps, glitches, and speed bumps lacing through and defining it.
boek